Nontarget analysis and fluorine atom balances of transformation products from UV/sulfite degradation of perfluoroalkyl contaminants. Issue 3 (25th January 2023) - Bowers, Bailey B.; Lou, Zimo; Xu, Jiang; De Silva, Amila O.; Xu, Xinhua; Lowry, Gregory V.; Sullivan, Ryan C.
Abstract : Per- and polyfluoroalkyl substances (PFAS) reduction via the hydrated electron yields highly fluorinated (and thus still concerning) transformation products, which can be characterized via nontarget analysis using high-resolution mass spectrometry. Abstract : Per- and polyfluoroalkyl substances (PFAS) are a class of thousands of highly fluorinated, anthropogenic compounds that are used in a wide variety of consumer applications. Due to their widespread use and high persistence, PFAS are ubiquitous in drinking water, which is of concern due to the threats these compounds pose to human health. Reduction via the hydrated electron is a promising technology for PFAS remediation and has been well-studied. However, since previous work rarely reports fluorine atom balances and often relies on suspect screening, some transformation products are likely unaccounted for. Therefore, we performed non-target analysis using high-resolution mass spectrometry on solutions of perfluorooctanesulfonate (PFOS), perfluorobutanesulfonate (PFBS), perfluorooctanoate (PFOA), and 2, 3, 3, 3-tetrafluoro-2-(heptafluoropropoxy)propanoate (GenX) that had been treated with UV/sulfite to produce hydrated electrons. We determined fluorine atom balances for all compounds studied, finding high fluorine atom balances for PFOS and PFBS. PFOA and GenX had lower overall fluorine atom balances, likely due to the production of volatile or very polar transformation products that were not measured by our methods. Transformation products identified by our analysis were consistent with literature, with a few exceptions. Namely, shorter-chain perfluorosulfonates (PFSA) and their H/F substituted counterparts were also detected from PFOS. This is an unexpected result based on literature, as no documented pathway exists for the formation of shorter-chain PFSA during UV/sulfite treatment. Furthermore, the nontarget approach we employed allowed for identification of novel, unsaturated products from the hydrated electron treatment of perfluorooctanesulfonate (PFOS) that warrant further investigation.